Real Flexibility and Financial Structure: An Empirical Analysis - MacKay, Peter (Review of Financial Studies, 2003)
I examine the empirical relation between real flexibility and financial structure. I test whether real flexibility increases debt capacity by lowering default risk and making assets more marketable or decreases debt capacity by facilitating risk shifting and asset substitution. I measure real flexibility as the sensitivity of marginal production and investment decisions to variations in the economic environment. I find that financial leverage is negatively related to production flexibility but positively related to investment flexibility. This split in results suggests that although asset substitution facilitated by investment flexibility can be prevented contractually, risk shifting facilitated by production flexibility is intractable. Copyright 2003, Oxford University Press.